Controllability of stochastic semilinear functional differential equations in Hilbert spaces - Dauer, JP; Mahmudov, NI (Academic Press Inc Elsevier Science, 2004)
In this paper approximate and exact controllability for semilinear stochastic functional differential equations in Hilbert spaces is studied. Sufficient conditions are established for each of these types of controllability. The results are obtained by using the Banach fixed point theorem. Applications to stochastic heat equation are given. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: approximate controllability; exact controllability; semilinear stochastic functional differential; equations; Banach fixed point theorem